A Preliminary Study of Employment of Engineers in Public Electricity Supply Undertakings: Present Positions and Basis for Estimating Future Requirements - Planning Commission (Planning Commission Government of India, 1957)
This study examines the employment patterns and future manpower requirements of engineers in public electricity supply undertakings in India, based on a preliminary survey conducted by the Scientific and Technical Manpower Division of the Planning Commission during 1957. The primary objectives were to analyze the relationship between installed generating capacity and engineering employment, establish normative standards for engineer requirements across different types of power stations, and estimate future workforce needs in alignment with the Second Five-Year Plan. The findings indicate that as of December 1955, public electricity supply undertakings employed 2,312 engineers, comprising both graduate engineers and diploma holders, with electrical engineers forming the majority. Significant variations were observed in engineer-to-capacity ratios across thermal, hydro, diesel, and bulk supply undertakings, with diesel stations exhibiting the highest manpower intensity. Based on established norms and projected growth in installed capacity, the study estimates that engineering employment would need to expand by approximately 91 percent by 1960 to meet operational and maintenance demands. The report further highlights sectoral and regional disparities in employment practices, noting that public undertakings tend to employ more engineers relative to capacity compared to private utilities. Against the backdrop of rapid expansion in power generation capacity and low per capita electricity consumption, the study underscores the importance of systematic technical manpower planning. It concludes by recommending more detailed surveys and refined norms to ensure an optimal balance of engineering skills, thereby supporting the efficient and sustainable development of India’s electricity sector.
Planning Commission Scientific and Technical Manpower Division
Planning Commission Scientific and Technical Manpower Division
Keywords: Employment of Engineers; Electricity Supply Undertakings; Technical Manpower Planning; Generating Capacity; Power Sector Workforce; Engineering Norms; Electrical Engineers; Diploma Holders; Installed Capacity Growth; Second Five Year Plan; Public Sector Utilities; Manpower Projections